Perlindungan Hukum Bagi Konsumen terhadap Produk Kecantikan Tidak Terdaftar BPOM yang Beredar di E-Commerce - Stephanie Patricia Prasetyo; Ariawan Gunadi (CV Rewang Rencang, 2024)
The advancement of information technology has increased the popularity of e-commerce in Indonesia, especially in the beauty product category. Ease of access and product variety make e-commerce a top choice for consumers. However, the lack of BPOM (Indonesian FDA) approval for certain beauty products sold online poses serious health risks for consumers. These unregistered products often contain harmful substances, which can cause side effects ranging from irritation to cancer risk. Consumers are often attracted by affordable prices and promotional offers without considering product safety. In this context, legal protection for consumers is crucial. Under the Consumer Protection Law and BPOM regulations, consumers have the right to safe products and accurate information. This study employs a normative juridical method to analyze consumer legal protection and possible legal actions when receiving unregistered beauty products. The findings indicate that, in addition to producers, e-commerce platforms are also responsible for the circulation of illegal products and must ensure that products sold comply with applicable legal standards.